Competition and prosociality: A field experiment in Ghana - Kerstin Grosch; Marcela Ibanez; Angelino C. G. Viceisza (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
Competitive bonuses are commonly used to promote higher productivity in the workplace. Yet, these types of incentives could have negative spillovers on coworkers' prosocial behavior in subsequent tasks. To investigate this question, we conduct a lab-in-the-field experiment in Ghana. In a between-subjects design, participants complete a real-effort task under a competitive, threshold, or random payment while holding payment differentials constant across treatments. Before and after, we measure prosociality through a public goods and a social value orientation game. Competition reduces prosociality when the dispersion of payments is high. However, when there is less at stake, competition does not affect prosociality.
Keywords: C93; D03; J33; 330; competitive payment; wage differences; prosociality; field experiment